2019
DOI: 10.1007/s13181-019-00739-6
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNA Profiles in Acetaminophen Toxicity

Abstract: Introduction Acetaminophen toxicity has been associated with elevation of microRNAs. The present study was to evaluate overall microRNA profiles and previously identified microRNAs to differentiate acetaminophen (APAP) toxicity from other causes of transaminase elevation. Methods This was an observational study of adults with presumed acetaminophen toxicity at presentation. Serum samples were collected every 12 hours during hospitalization. Total miRNAs were extracted from plasma and levels of 327 microRNAs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…In the early hours post ingestion in cases of acute paracetamol toxicity, the diagnosis of acute liver injury and the initiation of antidote treatment depends mainly on paracetamol serum level plotted on Rumak Mathew nomogram as the rise in liver transaminases is not seen except several hours post ingestion (Shankar & Mehendale, 2006;Olson, 2012) The role of microRNA-122 (miRNA-122) in the early detection of liver injury in patients with acute paracetamol toxicity is an area of increasing interest, as this small non-coding RNA molecule has been found to be involved in the regulation of liver homeostasis and is highly abundant in the liver (Bandiera et al, 2015). Elevated levels of miRNA-122 in the bloodstream can be indicative of liver damage and may serve as a potential biomarker for the early detection of liver injury (Wang et al, 2009;Carreiro et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In the early hours post ingestion in cases of acute paracetamol toxicity, the diagnosis of acute liver injury and the initiation of antidote treatment depends mainly on paracetamol serum level plotted on Rumak Mathew nomogram as the rise in liver transaminases is not seen except several hours post ingestion (Shankar & Mehendale, 2006;Olson, 2012) The role of microRNA-122 (miRNA-122) in the early detection of liver injury in patients with acute paracetamol toxicity is an area of increasing interest, as this small non-coding RNA molecule has been found to be involved in the regulation of liver homeostasis and is highly abundant in the liver (Bandiera et al, 2015). Elevated levels of miRNA-122 in the bloodstream can be indicative of liver damage and may serve as a potential biomarker for the early detection of liver injury (Wang et al, 2009;Carreiro et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al 2009 [168] first reported that serum levels of multiple miRNAs are altered in mice with APAP-induced liver injury, and these data were extended to APAP overdose patients by the research group of Kevin Park at the University of Liverpool two years later [169]. Since then, many miRNAs have been shown to increase or decrease in circulation in APAP hepatotoxicity [169][170][171][172][173][174], but miR-122 seems to display the largest and most consistent changes [175].…”
Section: Mirna-based Biomarkersmentioning
confidence: 99%